ZMIANY PRAWA ROLNEGO. TENDENCJE ROZWOJU - Budzionwski, Roman (Wydział Prawa i Administracji UAM, 2002)
The aim of this article is to determine the existing trends in the development of agricultural law as a branch of legislation. These trends shed light on the problems connected with the development of this branch of the law and scholarly discipline. The presented considerations are founded upon the assumption that observing the changes can help define certain regularities or tendencies in agricultural law development. Legislation development is undoubtedly connected with the development o f both the doctrine and agricultural law as a branch o f the legal system. In order to characterize the evolution from the traditional agricultural law towards the modern, or modernized agricultural law, and at the same time to pinpoint the existing developmental trends o f this branch o f the law, one should above all focus upon such phenomena as: a) gradual „piling up” of agricultural legislation (agricultural law dynamics); b) expansion of the regulated area, i.e. the agricultural law; c) changes of the legal influence methods (i.e. methods of publicizing agricultural law); d) Creation and evolution o f legal institutions within this branch of the law. The starting point and the axis of the considerations is the general assumption that the usual course of evolution is from traditional to modem agricultural law. While the former is usually associated with the past and is well-known and scientifically studied, the latter is connected with the present time and some further studies on this law are required.
MODIFICATIONS TO AGRICULTURAL LAW. DEVELOPMENT TRENDS